PEMBENTUKAN KARAKTER ANAK MELALUI HADITS NABAWI: PENDEKATAN HOLISTIK DAN MULTIDISIPLIN DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Nuratika, Nuratika; Alma’arif, Alma’arif (Jurnal Manajemen Pendidikan, 2025)
Children’s character education is a fundamental aspect of Islamic Religious Education (PAI), especially in the context of increasingly complex globalization challenges, the rapid negative impact of digital technology development, and the growing moral crisis. The Prophetic Hadith, as the second primary source of Islamic teachings after the Qur’an, plays a strategic role in the process of shaping children’s personalities and character comprehensively. The purpose of this study is to analyze the Prophetic Hadith in the formation of children’s character, using a holistic and multidisciplinary approach in PAI learning. This study employs a qualitative approach through library research. Primary data were obtained from authoritative Hadith collections, while secondary data were drawn from relevant books and national and international scholarly journals. The findings indicate that the Prophetic Hadith contains universal principles for shaping children’s character that transcend time and can be effectively internalized through integrative and holistic PAI learning. Furthermore, a multidisciplinary approach in learning reinforces the relevance of Hadith values in the context of students’ development. This article is expected to provide both theoretical and practical contributions to the development of Islamic Religious Education oriented toward the formation of children’s character.